Muslim-friendly railway services: concept and challenges of Malaysian Electric Train Service (ETS) - Abdul Halim, Siti Norhamimah; Harum, Ahmad Aiman; Jamaludin, Mohammad Aizat; Kartika, Betania (HH Publisher, 2020)
Muslim-Friendly Railway Services (MFRS) is a service that accommodates Muslims’ needs during travel. There are two basic needs of Muslims during travel, which are halal food and place for prayers. Therefore, it is important for MFRS to fulfil these two requirements. Besides halal food, beverage and Muslim prayer facility (musolla), other elements that can be included in MFRS are prayer time, Ka‘abah direction (qiblah), ablution capability (wudhu’), availability of prayer rug or mat, female prayer apparel, a copy of the Al-Quran, supplication guide (du‘a), segregation of gender and appropriate entertainment are discussed below. Qualitative research has been used in this study, consisting of data obtained through library research and semi-structured interviews. This paper attempts to study the concept of implementing MFRS in the Electric Train Service (ETS) by Malaysian Railways (KTMB). This study also deliberates on the challenges faced by ETS operation upon implementing the MFRS which are high cost for implementation, negative perception among non-Muslim passengers and the acceptance and implementation of the MFRS in Malaysia might be complicated. This study found that more awareness and knowledge on the MFRS should be increased and disseminated among ETS consumers and railway industry players to enhance transportation services according to Shariah principles. Perhaps this study could help to develop tourism sector in Malaysia thus increase the country’s income by attracting many tourists from outside and open many job opportunities.